Prediction of Trash in Aceh Province Using the Autoregressive Integrated Moving Average (ARIMA) Method - Nefo Preyandre; Dahlan Abdullah; Said Anshari (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The increase in trash production in Aceh Province presents challenges for trash management, particularly in planning adequate infrastructure. This study applies the Autoregressive Integrated Moving Average (ARIMA) model to predict trash volume in Aceh. The data utilized originates from the National Trash Management Information System (SIPSN) and the Central Bureau of Statistics (BPS) from 2020 to 2023. The prediction results indicate that ARIMA can capture the primary trends in trash volume but has limitations in accounting for seasonal fluctuations in certain trash categories. Accuracy evaluation using the Mean Absolute Percentage Error (MAPE) shows varying accuracy levels across trash types, with some categories requiring additional models to enhance accuracy. These findings are expected to support planning and policy for trash management in Aceh.